Erratum: an @international adult guideline for making clozapine titration safer by using six ancestry-based personalized dosing titrations, CRP, and clozapine levels - De Leon, Jose; Schoretsanitis, Georgios; Smith, Robert L.; Molden, Espen; Solismaa, Anssi; Seppälä, Niko; Kopeček, Miloslav; Švancer, Patrik; Olmos, Ismael; Ricciardi, Carina; Iglesias-Garcia, Celso; Iglesias-Alonso, Ana; et al. (Pharmacopsychiatry, 2022)
In the above-mentioned article, the spelling of 5 authors last names has been wrong and these names have been corrected.